(untitled) (Olhar de Professor, 2012)
This article is the result of research developed together with teachers working in public schools in the cities of Natal and Macaíba in the state of Rio Grande do Norte. The research focused on the place of media studies in teacher education from an emancipatory perspective. The research was carried out using a multi-referential approach and addressed this issue from a perspective of understanding how the role of media studies is situated within the Brazilian educational scenario and what elements are involved in the delimitation of its frontiers. One of the themes that emerged during the research was the different ways of referring to the media in the context of education - teaching resources, audiovisual resources, communication media, educational technologies and communication education technologies. What is discussed in this paper is that each of these terms carries with them a conception of education that contributes to a more (or less) emancipatory relationship with the media.